Stereotactic body radiation therapy for prostate cancer. (September 2011) - Ishiyama, Hiromichi; Teh, Bin S; Lo, Simon S; Mathews, Thomas; Blanco, Angel; Amato, Robert; Ellis, Rodney J; Mayr, Nina A; Paulino, Arnold C; Xu, Bo; Butler, Brian E
Stereotactic body radiation therapy (SBRT) is a promising treatment option for prostate cancer. Hypofractionation regimens, such as SBRT, may be more advantageous compared with conventional regimens because low αα:ββ ratio of prostate cancer has high sensitivity to dose per fraction. In addition, a smaller and tighter margin with SBRT is expected to provide a low toxicity rate without reducing tumor control. The purpose of this article is to examine radiobiological, technical and clinical aspects of SBRT for prostate cancer.